Ochrona oznaczeń geograficznych produktów rolnych i środków spożywczych w prawie międzynarodowym - Kapała, Anna (Wydawnictwo Naukowe UAM, 2007)
The paper concerns the protection of geographical indications for agricultural products and foodstuffs in international law. The aim of the deliberations is an attempt to define and evaluate the efficiency of international protection of geographical indications. The approach to the definition of geographical indications, the subject and the scope of protection, as well as the problem of deciding, by member states, which legal measures to take, and, above all, the regulations governing disputable issues such as: premises for the exclusion o f protection, the conditioning of the prohibition of protection on whether the consumer has been misled, the registration of geographical indications as trademarks, and exceptions made for special protection o f wines and spirits have been discussed. Finally, the influence of the TRIPS 'national treatment' and the 'most favoured nation clause' rules on the protection of geographical indications o f third countries in the European market have been presented. The paper ends with a conclusion already formulated in the literature that the level of protection of geographical indications provided for in the TRIPS Agreement is not satisfactory
PROTECTION OF GEOGRAPHICAL INDICATIONS OF AGRICULTURAL PRODUCTS AND FOODSTUFFS IN INTERNATIONAL LAW